My question is:

Given triangle $ABC$, where angle $C=90°$. Prove that the set $\{ s , s-a , s-b , s-c \}$ is identical to $\{ r , r_1 , r_2 , r_3 \}$.

$s=$semiperimeter, $r_1,r_2,r_3$ are the ex-radii.

Any help to solve this would be greatly appreciated.

  • $\begingroup$ and presumably $r$ is the inradius, which should be equal to $s-c$. $\endgroup$ – Henry Jun 10 '12 at 11:32
  • $\begingroup$ @Henry how did you get that? $\endgroup$ – mgh Jun 11 '12 at 9:57
  • $\begingroup$ I drew an example and measured the various lengths. $s$ is the ex-radius opposite $C$. It confirmed your statement, though it is not a proof. $\endgroup$ – Henry Jun 11 '12 at 16:04
  • $\begingroup$ The result is (the converse of) Amy Bell's proposition 3. What she calls "the formulas for the exradii" can be found on Wikipedia $\endgroup$ – Henry Jun 11 '12 at 21:38

This problem have some interesting fact behind so I use pure geometry method to solve it to show these facts:

first we draw a picture. fig1

$\triangle ABC$, $I$ is incenter, $A0,B0,C0$ are the tangent points of incircle. $R1,R2,R3$ is ex-circle center,their tangent points are $A1,B1,C1,A2,B2,C2,A3,B3,C3$.

FOR in-circle, we have $CA0=CB0=s-c,BA0=BC0=s-b,AB0=AC0=s-a$,

now look at circle $R2, BC2$ and $BA1$ are the tangent lines, so $BC2=BA1$,

for same reason, we have

$CA1=CB2,AC2=AB2$, and $CB2=AC-AB2$.

since $BA1=BC+CA1=BC+CB2=BC+AC-AB2,BC2=AB+AC2=AB+AB2$,

so we have

$BC+AC-AB2=AB+AB2$, ie$ AB2=\dfrac{BC+AC-AB}{2}=s-c=CB0, CB2=AC-AB2=AC-CB0=AB0=s-b$ .

with same reason, we have

$ AC2=BC0=s-b$,


above facts are for any triangles as we don't have limits for the triangle.

now we check $R1-A2-C-B1$, since $R1A2=R1B1=r1$, so $R1-A2-C-B1$ is a square! we get


with same reason , we get

$ r2=CB2=s-b$,

we also konw $r3=R3A3=CB3$ ,

since $\angle B3AC2=\angle R3AB3$($AR3$ is bisector), so $AC2=AB3$,

$ r3=CB3=AC+AB3=AC+AC2=b+s-b=s$,


$ r=IA0=CB0=s-c$

now we show the interesting fact:

$ r+r1+r2+r3=s-c+s-b+s-a+s=2s=a+b+c $

$ r^2+r1^2+r2^2+r3^2=(s-c)^2+(s-b)^2+(s-a)^2+s^2=4S^2+a^2+b^2+c^2-2s(a+b+c)=4S^2+a^2+b^2+c^2-2S*2S=a^2+b^2+c^2$

we rewrite the again:

In Right angle:

$ r+r1+r2+r3==a+b+c $

$ r^2+r1^2+r2^2+r3^2=a^2+b^2+c^2$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.